Patient and family opinions and preferences of visiting practices in a burns intensive care unit - Webber, Lauren Bridget (My University, 2021)
Purpose: The purpose of this study was to describe the opinions and preferences of family members and patients on visiting practices in the Burns ICU setting of a level 1 private sector hospital in Gauteng, South Africa. Background: Many visiting practices have been implemented throughout the years within Intensive Care Units. Although there are numerous benefitsto patients, family members and healthcare workers within the ICU, especially specialised units as burns, regarding family and patient-centered visitation, controversy still surrounds this issue, thus it is important to explore the opinions and preferences about visitation practices. Methods: A quantitative, non-experimental, descriptive and cross-sectional survey design was used to describe the patient and family members’ opinions and preferences of visiting in a Burns ICU. The final sample consisted of N= 51 respondents, thus giving a response rate of 96.2% for the study. Data was collected from the patients and family members using a validated questionnaire developed by Ramnath (2007). Data was analysed using descriptive and inferential statistical testsusing t-tests and Chi-square analysis. Testing was done at the 0.05 level of significance. Results: The majority of the respondents preferred a longer visiting time compared to shorter and more frequent visits. Thirty nine point two percent (39.2%) of theparticipants reported wanting to stay longer and 29.4% of the respondents would have preferred the visits to be more frequent. Fifty nine point three percent, (59.3%) of the family respondents strongly agreed that visiting hours in the Burns ICU should not be restricted and 14.8% strongly disagreed and felt that it should be restricted. Fifty one point nine percent (51.9%) disagreed that imposing restricted visiting hours on a family member of a critically ill loved one is acceptable. Conclusion: Open visiting hours was found most beneficial to both the patients and their family member’s ion this study. It was largely reported in this study that both the family members and the patients had reduced anxiety levels during these open visits. It was also identified that patients found their recovery easier as their visitors helped to distract them from their predicament as well as support them through their recovery. Although it was reported that the staff were friendly, not all the patients and family members felt sufficiently supported or that they were provided enough information and education on the patients’ condition.
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, in partial fulfilment of the requirements for the degree of Master of Science in Nursing, 2021